2015
DOI: 10.1007/s00415-015-7844-y
|View full text |Cite
|
Sign up to set email alerts
|

Features of anti-aquaporin 4 antibody-seropositive Chinese patients with neuromyelitis optica spectrum optic neuritis

Abstract: The detection of anti-aquaporin-4 autoantibody (AQP-4 Ab) is crucial to detect patients who will develop neuromyelitis optica (NMO); however, there are few studies on the AQP-4 Ab serostatus of patients with neuromyelitis optica spectrum ON. We analyzed the clinical and paraclinical features of neuromyelitis optica spectrum ON patients in China according to the patients' AQP4-Ab serostatus. 125 patients with recurrent and bilateral ON with simultaneous attacks were divided into AQP-4 Ab-seropositive and -seron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
1
11
1
Order By: Relevance
“…Nevertheless, we found 17.2% in the idiopathic group which is higher than the NMOSD group and the MS group. The present study showed the majority of optic neuritis patients associated with demyelinating disease had normal disc appearance (89.6% in NMOSD, 78.3% in MS), which is quite different compared to other studies [ 2 , 24 , 41 ]. The final report by ONTT group about MS risks after optic neuritis concluded that patients without MRI brain lesion at the beginning of isolated optic neuritis attack did not develop MS when baseline exam showed severe optic disc swelling, disc or peripapillary hemorrhages, retinal or macular exudates and absence of pain.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we found 17.2% in the idiopathic group which is higher than the NMOSD group and the MS group. The present study showed the majority of optic neuritis patients associated with demyelinating disease had normal disc appearance (89.6% in NMOSD, 78.3% in MS), which is quite different compared to other studies [ 2 , 24 , 41 ]. The final report by ONTT group about MS risks after optic neuritis concluded that patients without MRI brain lesion at the beginning of isolated optic neuritis attack did not develop MS when baseline exam showed severe optic disc swelling, disc or peripapillary hemorrhages, retinal or macular exudates and absence of pain.…”
Section: Discussioncontrasting
confidence: 99%
“…In optic neuritis patients, AQP4-IgG was found in 0-11.4% patients in western countries and 9 – 35.2% in Asian countries [ 9 - 16 , 22 , 23 ]. This rate increased to 20-69.2% in recurrent optic neuritis [ 10 , 13 , 24 ]. We found 57.4% of the patients having at least one recurrent attack.…”
Section: Discussionmentioning
confidence: 99%
“…Serum AQP4 antibody examination was performed by a live cell-staining immunofluorescence technique using transiently transfected AQP4-expressing cells, as described previously by our group 15. Sera were screened for antinuclear antibody (ANA), anti-Sigren syndrome A and anti-Sigren syndromeB (SSA and SSB), major histocompatibility complex-B27, rheumatoid factor, anticardiolipin antibodies (ACLs and b2-GPI), and antineutrophil cytoplasmic antibodies (ANCA) in the Examination Center for Biomedical Research of PLAGH.…”
Section: Methodsmentioning
confidence: 99%
“…Serum and CSF were collected from all patients for NMO-IgG testing. The presence of NMO-IgG was analysed by both commercial enzyme-linked immunosorbent assays (ELISA) kits and extracellular live cell-staining immunofluorescence technique using transiently transfected AQP4-expressing cells, as described in our previous reports (Li et al 2014(Li et al , 2015. All patients underwent a comprehensive ophthalmic examination and standardized treatments.…”
Section: Nmo-igg Testing and Visual Measurementsmentioning
confidence: 99%